DEVELOPMENT OF BARI-2011: A HIGH YIELDING, DROUGHT TOLERANT VARIETY OF GROUNDNUT (Arachis hypogaea L.) WITH 3-4 SEEDED PODS - Naeem-ud-Din; M. Tariq; M. K. Naeem; M. F. Hassan; G. Rabbani; A. Mahmood; M. S. Iqbal (Journal of Animal and Plant Sciences, 2012)
BARI-2011 is the first groundnut variety in Pakistan which was developed through hybridization procedure. This high yielding groundnut variety recently approved was developed from a cross PW x Chico. The cross was attempted during 1992 at BARI, Chakwal. F1 to F7 generations were raised at Barani Agricultural Research Institute (BARI), Chakwal. Selection was done following pedigree method for high yield, more number of seeds per pod and good plant type. On the basis of its performance in yield trials, Punjab Seed Council approved it as a commercial variety under the name BARI-2011 for general cultivation in January, 2011. This variety on an average gave 26.1% better yield than all check varieties; No.334, Chakori, BARD- 479, BARI-2000 and Golden. Average and potential pod yield of BARI-2011 is 2500 and 6300 kg ha-1, respectively. In addition, BARI-2011 is drought tolerant, has more shelling percentage and has resistance against Cercospora Leaf Spot (Tikka disease) and root rot. Variegated seed coat colour and 3-4 seeded pods are the distinguishing characteristics from other existing groundnut varieties.
Keywords: Groundnut; High yielding; Drought tolerant; Variegated; Seed Coat Colour; 3-4 seeded pods.